Karakteristik Ibu Menyusui dalam Persepsi dan Perilaku terhadap Terapi Komplementer untuk Produksi ASI di Kalimantan Utara - Nurrahmi Umami; Ririn Ariyanti; Annisa Eka Permatasari, (Bunda Edu-Midwifery Journal (BEMJ), 2025)
Breast milk (ASI) is the primary source of nutrition for infants and plays a vital role in their growth and development. However, many breastfeeding mothers experience challenges, particularly related to low milk production. One emerging solution is the use of complementary therapies. This study aimed to identify the characteristics of breastfeeding mothers and their perceptions and behaviors towards complementary therapy to enhance breast milk production in the working area of Pantai Amal Public Health Center, Tarakan City, North Kalimantan. A descriptive quantitative design was used with 62 respondents selected through simple random sampling. Data were collected using observation sheets and open interviews with 10 selected mothers. The results showed that most respondents were of reproductive age (20–35 years), had basic to intermediate education, and were not formally employed. Knowledge about complementary therapy was generally low, and most respondents had never consciously used it. However, most expressed interest in trying complementary therapy if provided with appropriate education by health workers. These findings highlight the need for targeted health education interventions to improve maternal health literacy regarding complementary therapies in breastfeeding.